ANALISA POTENSI ENERGI ANGIN DI PANTAI LHONG KABUPATEN ACEH BESAR MENGGUNAKAN DISTRIBUSI WEIBULL - Herdian Saputra (VOCATECH: Vocational Education and Technology Journal, 2022)
Aceh Province in the National Energy General Plan is targeted in 2050 for the development of new renewable energy wind power plants to reach 894 MW of power. This wind energy potential still needs to be surveyed or further researched for the suitability of its development location so as to produce the best position as a wind power plant. This study aims to analyze the wind potential on the Lhong coast, Aceh Besar District, Aceh Province using the Weibull distribution and using the wind speed from the ECMWF. The average wind speed distributed by weibull at the location reaches 2 m/s with a frequency of 26% and a speed of 3 m/s with a frequency of 25%. The power generated from the wind potential in the Lhong coastal area of Aceh Besar Regency is 32.411 watt meters with electrical energy produced 168,364 kwh/m/year, which belongs to the category of low-class wind as a wind power plant.Keywords:Power Generation, Renewable Energy, Wind Energy Potential.